Making spaces for community development - Pitchford, Michael ca. 20./21. Jh (The Policy Press, 2008)
Dealing directly and exclusively with the issue of older workers, this book brings together up-to-the-minute research findings by many of the leading researchers and writers in the field, exploring key issues that will influence public policy in the UK and beyond